(untitled) (Research, Society and Development, 2022)
Objective: To identify, in the scientific literature, educational games used for the continuing education of health professionals, in order to characterize them. Method: this is an integrative review performed by searching the PubMed, Web of Science databases and the Regional Portal of the Virtual Health Library. The search resulted in 13 studies published between 2017 and 2021. Results: The games used in the continuing education of health professionals were physical resources (38.46%), digital (38.46%) and simulators (23.08%). Regarding the theme addressed through such instruments, 30.77% addressed the daily procedures of the performance of nursing professionals and 61.54% were elated to the specific needs of the Intensive Care Unit, Neonatology, Obstetric Center, Surgical Center or the Basic Health Unit. Conclusion and Implications for Practice: The literature found demonstrates that the use of active methodologies provides better learning results, as playful activities facilitate cognition and encourage creativity and public participation. Thus, it emphasizes the importance of alternative resources and active methodologies in the development of educational activities aimed at health professionals, in order to explore potential and promote changes in the resolution of adverse situations present in health environments.